2020
DOI: 10.1073/pnas.1909649117
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibition of DUX4 expression with antisense LNA gapmers as a therapy for facioscapulohumeral muscular dystrophy

Abstract: Facioscapulohumeral muscular dystrophy (FSHD), characterized by progressive muscle weakness and deterioration, is genetically linked to aberrant expression of DUX4 in muscle. DUX4, in its full-length form, is cytotoxic in nongermline tissues. Here, we designed locked nucleic acid (LNA) gapmer antisense oligonucleotides (AOs) to knock down DUX4 in immortalized FSHD myoblasts and the FLExDUX4 FSHD mouse model. Using a screening method capable of reliably evaluating the knockdown efficiency of LNA gapmers against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 37 publications
(61 reference statements)
0
53
0
Order By: Relevance
“…These have been rapidly adopted by the FSHD research community and enabled many studies of pathological mechanisms and pre-clinical testing of therapeutics. In particular, these new model systems have provided platforms for studying cutting-edge molecular therapies, including CRISPR- and antisense oligonucleotide-based modulation of DUX4 or other gene expression ( Chen et al, 2016 ; Giesige et al, 2018 ; Himeda et al, 2016 , 2018 ; Lim et al, 2015 , 2020 ; Marsollier et al, 2016 ; Wallace et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…These have been rapidly adopted by the FSHD research community and enabled many studies of pathological mechanisms and pre-clinical testing of therapeutics. In particular, these new model systems have provided platforms for studying cutting-edge molecular therapies, including CRISPR- and antisense oligonucleotide-based modulation of DUX4 or other gene expression ( Chen et al, 2016 ; Giesige et al, 2018 ; Himeda et al, 2016 , 2018 ; Lim et al, 2015 , 2020 ; Marsollier et al, 2016 ; Wallace et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…All in vitro and in vivo FSHD models confirmed a significant decrease of DUX4-fl transcript expression levels associated with an inhibition of DUX4-fl activity, as multiple target genes (TRIM43, MBD3L2, and ZSCAN4) were also efficiently down regulated [46], thereby confirming the therapeutic properties of AOs and morpholinos in correcting DUX4-mediated toxicity in skeletal muscle. More recently, a locked nucleic acid (LNA) gapmer antisense oligonucleotide was developed to silence DUX4 [50]. LNA gapmers present a central DNA gap flanked by LNA stretches to increase the binding affinity to the target RNA.…”
Section: Targeting Dux4 Mrnamentioning
confidence: 99%
“…But no muscle phenotype was observed, no DUX4 protein was revealed after immunostaining, and there was no activation of the murine DUX4 target gene Wfdc3. Despite the very low level of DUX4 expression and the absence of downstream effects, this mouse model was recently used to assess antisense LNA gapmer efficacy [50].…”
Section: • D4z4-25/smchd1mommed1 Mice (2018)mentioning
confidence: 99%
“…Several strategies to accomplish this are currently under development, including increasing the heterochromatin status of the DUX4 DNA locus to prevent its expression and inhibiting the DUX4 mRNA before it can be translated into protein. 18 , 23 , 24 , 25 , 26 , 27 , 28 , 29 Indeed, our lab previously used gene therapy to deliver artificial microRNAs (miRNAs) engineered to knock down the DUX4 mRNA via RNA interference (RNAi) in vitro and in vivo . 10 , 30 , 31 Other groups demonstrated that antisense oligonucleotides (ASOs), designed to mask splice sites and/or the poly(A) signal, could interfere with DUX4 mRNA production and suppress full-length DUX4 expression in FSHD cells.…”
Section: Introductionmentioning
confidence: 99%
“… 10 , 30 , 31 Other groups demonstrated that antisense oligonucleotides (ASOs), designed to mask splice sites and/or the poly(A) signal, could interfere with DUX4 mRNA production and suppress full-length DUX4 expression in FSHD cells. 18 , 23 , 24 , 25 , 29 The system we describe here has some similarity to these ASO studies because we utilize antisense sequences in our designs. However, our approach is distinct because it uses a recombinant U7 small nuclear RNA (U7-snRNA) expression system to produce antisense sequences, overcoming some major limitations of ASOs, such as inefficient delivery to muscle and a requirement for lifelong administration.…”
Section: Introductionmentioning
confidence: 99%